Logam Berat Pb Pada Tanah Sawah Dan Gabah Di Sub-Das Juwana Jawa Tengah - Mulyadi Mulyadi (Faculty of Agriculture, Pattimura University, 2013)
Juwana sub-watershed is a downstream region of the watershed Jragung Tuntang Serang Lusi and Juwana (Jratunseluna). Upstream watershed conservation and the middle of the forest or shrub which is cultivated to vegetable farm will accelerate the degradation of water resources and aggravate the residues of fertilizer and pesticide pollution into the watershed downstream. Soil (sediment) carried by surface runoff is also a major agent of the carrier pollutants in the runoff. Identification of heavy metal content of Pb in soil and grain in Sub-watershed wetland Juwana was conducted in 2009 by survey method. The research objective was to get the data and distribution of heavy metals Pb at sub-watershed wetland Juwana. Surveys and soil sampling grain was approached along Sub-watershed, land forms and sources of contaminants, thus representing samples taken at certain areas were considered homogeneous. Determining the location of the sample in this study will be used as the basis of information in making the map.. The results showed that the metal content of Pb in soils ranged from 0.23 to 2.89 ppm, and Pb in the grain ranged from 0.23 to 1.23 ppm, below the threshold determined value by WHO (2 ppm).